Critical links between arts activity participation, school satisfaction and university expectation for australian high school students - Geagea, A.; MacCallum, J.; Vernon, Lynette; Barber, B. (2017)
© 2017 The University of Newcastle, Australia. Positive school experiences increase school satisfaction and educational aspirations and, are important developmental opportunities for adolescents. Associations between time-varying school-based arts participation, students’ school satisfaction and university expectation were investigated using data collected from 1,215 students in 29 Western Australian high schools. Associations between school-based arts participation and school satisfaction, and school-based arts participation and university expectation were tested using latent growth curve analyses. Positive associations were found between school-based arts participation and time-specific variations in school satisfaction and university expectation in each year of activity participation. Higher levels of school satisfaction and university expectation were reported above and beyond individual-specific underlying developmental trajectory for these outcomes, controlling for socioeconomic status. Policy implications and practice are discussed in the context of arts provision for Australian schools.